Development of a recombinant genotype-matched live attenuated vaccine against genotype VII Newcastle disease virus - Bello, Muhammad Bashir (2018)
Newcastle disease is a highly contagious viral disease of birds considered as one of the most important militating factors against poultry production all over the world. Current control strategies against the disease rely on the use of vaccines developed more than six decades ago. Although those vaccines are still effective by virtue of the fact that all Newcastle disease viruses (NDV) belong to the same serotype, they neither provide a complete protection in commercial chickens, nor do they block the replication and shedding of the virulent virus following infection with genotype VII NDV. Phylogenetically, the vaccines are classified as either genotype I or II, and are evolutionarily divergent from genotype VII isolates which have been the most predominantly circulating NDV strains in Malaysia and many parts of the world for the past 20 years. Therefore in the present study, reverse genetics technology was applied to genetically attenuate the pathogenicity of a recently isolated virulent Malaysian NDV strain IBS025/13. First and foremost, in silico nucleotide substitutions were made on the complete genome sequence of NDV strain IBS025/13, in order to modify the fusion protein (F) cleavage site of the virus from the virulent polybasic (RRQKRF) to avirulent monobasic (GRQGRL) amino acid motifs. Unique MluI and SgrDI enzyme sites were also created at the P-M junction in order to facilitate future expression of foreign genes using the NDV backbone. The modified full length sequence (15.2 kb) was then entirely synthesised (GenScript, USA), subcloned into pOLTV5 transcription vector under the transcriptional control of T7 promoter and then named pOLTV5-mIBS025. Furthermore, expression plasmids for the NDV’s minimum replication machinery (NP, P and L genes) were constructed in pCIneo mammalian expression vector and named pCIneo-NP, pCIneo-P and pCIneo- L respectively. These constructs, collectively referred as helper plasmids, were later tested for functionality in reverse genetics experiments using minigenome rescue system. Next, baby hamster kidney (BHK-21) cells stably expressing T7 RNA polymerase were co-transfected with the mixture of the helper plasmids and pOLTV5- mIBS025 at an optimized ratio (1:0.5:0.25:0.2μg of POLTV5-mIBS025: pCineo-NP: pCIneo-P: pCIneo-L respectively). Interestingly, a recombinant virus designated NDV mIBS025, was successfully rescued following amplification in specific-pathogen-free (SPF) embryonated eggs, as evidenced by positive hemagglutination reaction. To confirm the identity of the recombinant virus, reverse transcription polymerase chain reaction (RT-PCR) was used to amplify a partial F gene region encompassing the cleavage site. DNA sequencing of the amplicons confirmed the presence of the engineered monobasic F cleavage site. Further biological characterization indicate that the recombinant virus has completely lost its pathogenicity as determined by the mean death time (MDT) in SPF embryonated eggs (150.4 hours) and the intracerebral pathogenicity index (ICPI) (0.0) in one-day old SPF chickens. Interestingly, when the recombinant virus was sequentially passaged in SPF eggs, it was found to not only maintain the monobasic F cleavage site, but also retained its attenuated phenotype after five consecutive passages, indicating the stability of the newly acquired attenuated phenotype. Finally, when one-day old SPF chickens were immunised with either 6log10 EID50 LaSota or the recombinant NDV mIBS025, a steadily increasing antibody titer was observed in both groups from 0-21 days post immunization, as determined by hemagglutination inhibition test using either genotype II or genotype VII NDV isolates as the HA antigen. Moreover, birds vaccinated with either LaSota or the recombinant NDVmIBS025 at the dose of 106 EID50 were completely protected against morbidity and mortality following experimental challenge with a lethal dose of the virulent genotype VII NDV strain IBS002/11. However, while both vaccines reduced the cloacal and oropharyngeal virus shedding compared to the unvaccinated group, the recombinant NDV mIBS025 significantly reduced both the duration and load quantity of the virus shed compared to the LaSota vaccine. In conclusion, reverse genetics has been used to generate a genotype-matched live attenuated vaccine candidate based on the recently circulating virulent NDV IBS025/13. Immunogenicity assessment indicates that the vaccine induced a high antibody titer capable of protecting chicken against the virulent genotype VII NDV challenge. The vaccine also appears to be more promising in terms of reducing the shedding of the virulent virus post challenge.